Two new species of Trichocladium Harz. from India - I.K. KUNWAR and D.K. AGARWAL, C. MANOHARACHARY, N. KRISHNA RAO (Indian Phytopathology, 2006)
Two new fungal species namely Trichocladium sigmoidea sp. nov. and T. palmae sp. nov. associated with some litter samples of forest localities of Andhra Pradesh, India are described here.